Quantification Of Endogenous Anabolic Androgenic Steroids Using Gas Chromatography Tandem Mass Spectrometry: An Application Of Steroid Profile From Eurycoma Longifolia Administration - Abushareeda, Wadha Masoud (2011)
A method was developed using gas chromatography tandem mass spectrometry (GC/MS/MS) to quantify the levels of endogenous androgenic anabolic steroids (EAAS) including testosterone, dehydroepiandrosterone, 4-andro -stenedione, 5-androstenediol, dihydrotestosterone and other related metabolites like androsterone, etiocholanolone, 5-α-androstandiol and 5-β-androstandiol in urine samples. The steroids were extracted using SPE method followed by LLE and analyzed by GC/MS/MS. Multiple Reaction Monitoring (MRM) was adopted for the analysis, using two MRM transitions as the qualifier ions and one MRM transition as the quantifier ion for each analyte. The linearity, extraction recovery, LOD, intra- and inter–day precision and accuracy as well as robustness of the method were validated. The correlation coefficients (r2) obtained was higher than or equal to 0.993 for all the compounds. The recoveries achieved using the method were higher than 70% for all analytes The limits of detection that was obtained using the method described in the present study ranged from 0.1 to 0.2 ng/mL. The limits of quantification ranged from to 0.5 to 1 ng/mL. The results showed good precision; where CV < 8% and accuracy ≥ 80% for all compounds in all assayed levels. The validation results showed that the analytical method used in this study to quantify the investigated anabolic steroids in urine has complied with the criteria of the validation for quantitative methods according to WADA ISL and NATA Technical Note.